2012
DOI: 10.1007/s13244-012-0151-6
|View full text |Cite
|
Sign up to set email alerts
|

Grading and characterization of soft tissue tumors on magnetic resonance imaging: the value of an expert second opinion report

Abstract: ObjectiveTo retrospectively compare the accuracy of the initial MRI (magnetic resonance imaging) report of referring radiologists and the second opinion report.Material and methodsMRI of 155 patients presenting with a soft tissue tumor (STT) in a single large community center were referred for inclusion in the Belgian Soft Tissue Neoplasm Registry (BSTNR). The initial report and the second opinion report were made independently. Histopathology (gold standard) was obtained in 90 patients (group 1). In 65 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…The favored anatomical site is the thigh (30%) . Hibernomas are usually described as arising from the subcutaneous tissues, approximately 10% are intramuscular in location …”
Section: Discussionmentioning
confidence: 99%
“…The favored anatomical site is the thigh (30%) . Hibernomas are usually described as arising from the subcutaneous tissues, approximately 10% are intramuscular in location …”
Section: Discussionmentioning
confidence: 99%
“…For example, small lipomas were referred based on ultrasound scans performed by any qualified provider (AQP), despite clear NICE guidance ( Figure 5). Vanhoenacker et al 16 recently reported that a second "expert" opinion increases the accuracy in the diagnosis of STT on MRI with fewer false-positive diagnoses. This adds further evidence to having a triage service run by speciality radiologists providing "expert" opinion to manage MDT referrals, which are often from referrers inexperienced with diagnosing a STS.…”
Section: Discussionmentioning
confidence: 99%
“…A second opinion report by a center with major expertise in STTs may improve the overall accuracy of grading and characterization from 83% up to 92%. 10 The role of advanced MR techniques such as diffusionweighted imaging, diffusion tensor imaging, and MR spectroscopy for tumor characterization and follow-up after treatment is still debated. 11…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Because MRI of other malignant STTs is mostly nonspecific, tissue-specific diagnosis based on imaging alone is often illusive. 6,10 The main task of the radiologist, however, is to make the differential diagnosis between benign and potentially malignant lesions (►Table 4) and to refer patients with potentially malignant lesions to centers with special expertise in the diagnosis and management of STTs (►Figs. 19 and 20).…”
Section: Malignant Tumorsmentioning
confidence: 99%